ANALISIS OUTAGE COST DI PT. TELKOM PURWOKERTO WITEL JATENG BARAT SELATAN - , EZA ADWIN RAAFII, Ir. Bambang Sugiyantoro, M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The rapid development of telecommunications companies forced to provide continuity of access to telecommunications networks optimally, such as in the provision of fixed and mobile phone services are increasingly expanding from year to year. Surely, this telecom company also has an important role in national economic development and are now beginning to do a more modern network renewal . However, in its development, there are some problems which pretty much felt by the telecom service providers related to the availability of electricity supply load consumers of telecommunications users. Problem that is often felt that the frequent occurrence of power outages so do not get the maximum service delivery outcomes. Among business enterprises, power outage affects the yield reduction provision of services that impact on company turnover obtained . Increasingly frequent power cuts, the outcomes provision of telephone services and declining corporate earnings earned will be smaller. Another impact is the number of consumer complaints related to telecommunications users frequent interruptions in telephone networks due to a power outage so the impact on the telecom company's inability to deal with telecommunication networks. Until now there is no literature about outage cost in telecommunication industries during the power outage. So that, need formulating of power outage cost. This research contains the outage cost of a telephone-related industry, PT. TELKOM Purwokerto WIiTel Jawa Tengah Barat Selatan during the power outage. Observations were made by calculating the non-profit earned by PT. TELKOM Purwokerto is when outages for 1 hour then it obtained loss of Rp. 4,127,191.20, then when experiencing power outage for 10 hours, PT TELKOM Purwokerto got a loss of Rp. 41,271,912.00 and when the power cuts for 24 hours (a day) then the losses obtained at Rp. 99,052,588.80. By this script can be known the outage cost of wood industries especially telecommunication service industry during the power outage, give more reference about the outage cost of telephone-related industries during the power outage. With the use of generator (Diesel Engine Generator) can reduces losses reached 57,84%.